Analisis Pengelolaan Kelas Bahasa Inggris Pada Masa Covid 19 Di Pondok Pesantren Kabupaten Lombok Timur - Mashur; Taufan Iswandi; Lalu Nurul Yaqin (LPPM Universitas Gunung Rinjani, 2023)
The purpose of this study is to explore how teachers in Pesantren manage classes and learning problems in Pesantren with the uniqueness of the system from the perspective of English teachers. This research method is qualitative research with a case study approach. The data was collected through observation and deepened through semi-structured interviews, Focus Group Discussions (FGDs), with English teachers at Islamic boarding schools. The results of this study in relation to class management are categorized into: eight main themes, namely: (1) Challenges to student participation and motivation, (2) Management of student behavior: Between punishment and encouragement, (3) Use of three languages in the classroom, (4) teacher performance as a source of challenges in classroom management, (5) Teacher discipline: breaking the rules due to low salaries, (6) teachers are not English majors, but was forced to teach English, (7) time management, and (8) manage large classes.